Candidate effector proteins of the necrotrophic apple canker pathogen Valsa mali can suppress BAX-induced PCD - Li, Zhengpeng; Yin, Zhiyuan; Fan, Yanyun; Xu, Ming; Kang, Zhensheng; Huang, Lili (Frontiers in Plant Science, 2015)
Canker caused by the Ascomycete Valsa mali is the most destructive disease of apple in Eastern Asia, resulting in yield losses of up to 100%. This necrotrophic fungus induces severe necrosis on apple, eventually leading to the death of the whole tree. Identification of necrosis inducing factors may help to unravel the molecular bases for colonization of apple trees by V. mali. As a first step toward this goal, we identified and characterized the V. mali repertoire of candidate effector proteins (CEPs). In total, 193 secreted proteins with no known function were predicted from genomic data, of which 101 were V. mali-specific. Compared to non-CEPs predicted for the V. mali secretome, CEPs have shorter sequence length and a higher content of cysteine residues. Based on transient over-expression in Nicotiana benthamiana performed for 70 randomly selected CEPs, seven V. mali Effector Proteins (VmEPs) were shown to significantly suppress BAX-induced PCD. Furthermore, targeted deletion of VmEP1 resulted in a significant reduction of virulence. These results suggest that V. mali expresses secreted proteins that can suppress PCD usually associated with effector-triggered immunity (ETI). ETI in turn may play an important role in the V. mali–apple interaction. The ability of V. mali to suppress plant ETI sheds a new light onto the interaction of a necrotrophic fungus with its host plant.